(untitled) (Biological Sciences - PJSIR, 1997)
In order to make a detailed assessment of the prevailing traffic noise in the Karachi city, this survey was conducted and traffic noise data was collected at 20 different sites, continuously for 12 hrs. at each site. The collected data has been analyzed for average background (Lyo)’ average (Lso) and average peak (LJO) values and results are discussed with reference to some international criteria for community annoyance and existing legislation thereon in Pakistan.